A dynamic model of authority in organizations - Bingbing Li; Manuel Förster (Bielefeld University, Center for Mathematical Economics (IMW), 2025)
In our principal-agent model, the principal can repeatedly delegate authority to an agent with uncertain preferences or take the decisions himself. The principal learns the state at the end of each period and then updates his belief about the agent's bias based on the decision implemented if he delegated authority. We demonstrate that equilibria are characterized by an "imitation" interval of agent types (biases) who mimic less biased types in order to be retained. Interestingly, the principal generally benefits from the agent's imitation compared to a benchmark. Furthermore, comparative statics reveal that, surprisingly, the principal may be worse off with better information. Finally, an extension to finitely many periods shows that the imitation interval gradually shifts, such that agent types within the interval imitate less biased types.
urn:nbn:de:0070-pub-30071276
Keywords: D23; D82; D83; D73; C72; 330; Delegation; preference uncertainty; private information; dynamic game; organizational design